Effects of aluminosilicate mineral nano-clay fillers on polysulfone mixed matrix membrane for carbon dioxide removal - Oh, P.C. (Penerbit UTM Press, 2014)
Over the last few decades, significant improvements in the performance of polymeric membranes for gas separation have been made. Nevertheless, the existing membrane materials need to be enhanced in order to fully exploit their gas separation application opportunities on industrial scale. Mixed matrix membrane which combines the advantages of the highly selective fillers and desirable properties of the polymer matrix is explored to overcome the trade-off trend between gas permeability and selectivity. This paper describes the effect of aluminosilicate mineral nano-clay fillers on polysulfone (PSF) mixed matrix membrane. In this study, different types of montmorillonite (MMT) nano-clays were used as fillers to fabricate asymmetric flat sheet mixed matrix membrane (MMM) via dry-wet phase inversion method. The interaction between the type of organoclay and its loading is also studied. The synthesis of MMM required N-methyl-2-pyrrolidone (NMP) as solvent and deionized water as coagulant. The fabricated MMMs were characterized by thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC) and field emission scanning electron microsropy (FESEM). Thin asymmetric membrane with dense skin layer and porous sub-structure was successfully fabricated. Results showed enhancement in MMM stability relative to neat PSF membrane. It is also found that higher nano-clay loading resulted in significant agglomeration, nevertheless, there appears to be improved adhesion between the polymer and nano-clay. Â© 2014 Penerbit UTM Press. All rights reserved.